Multiple glomus tumors in left hand digits: a case report with literature review - Neupane, Bikash; Wahegaonkar, Abhijeet; Jangale, Ajit; Patil, Chaitanya Karande; Bansode, Anup; Khandediya, Bhakti (International Journal of Research in Orthopaedics, 2026)
Glomus tumors are rare, benign vascular neoplasms that arise from the neuromyoarterial glomus body, most commonly occurring in the subungual region of the fingers. Despite their small size, which causes disproportionate symptoms characterized by severe localized pain, pinpoint tenderness, and cold sensitivity, they often lead to delayed or missed diagnosis. This case report is of a 48-year-old male with a 20-year history of localized pain in the left index, ring, and small fingers. He had visited multiple healthcare centers and received various treatments, but not relief. On detailed history and physical examination, with visual analogue scale (VAS) 9/10 findings were suggestive of a glomus tumor. Magnetic resonance imaging (MRI) confirmed the diagnosis and precisely localized the lesion. The patient underwent complete surgical excision, and histopathological examination of the specimen confirmed a glomus tumor. Postoperatively, the patient experienced immediate symptomatic relief, with a VAS 1/10. with no recurrence observed during nine months of follow-up. This case highlights the presence of a multiple-digit-long-standing glomus tumor in the left hand that remained undiagnosed and undertreated for a long time, the presence of multiple glomus tumors in the same hand digits is rarely reported in the literature. This case highlights an rare presentation of the highest reported number of glomus tumors involving multiple digits of a single hand.